Faktor yang Mempengaruhi Biaya Terapi Pada Pasien Fraktur Radius Ulna Dengan Pembedahan Orif dan Kesesuaian Dengan Tarif INA-CBG’S Di RSUD Kabupaten Sukoharjo - Mayang Aditya Ayuning Siwi; Tri Murti Andayani; Rina Herowati (Jurnal Farmasi Indonesia, 2016)
Drug management is an important aspect in pharmaceutical services. Drug procurement is one stage in the hospital drug management. The purpose of this study is to obtain an overview and analyze drug procurement in pharmacy department of RSUD Gambiran Kota Kediri period 2016. This research is a descriptive study with data collection by retrospective based on period 2016 for primary data and for secondary data interview with relevant department drug management on procurement analyzed by Depkes RI and research results before. The result showed that the drug procurement in RSUD Gambiran Kota Kediri using the financial resources BLUD, DAU and DBHCT with direct method and E-procurement. The results analysis drug procurement shows: percentage of the funds available at the overral required 99,12%, percentage of the allocation drug procurement 16,53%, frequency of the procurement of each drug items 4 times/ year by 94,96%, 16 times/ year by 7,73% and 32 times/ year by 3,22%, and long delays payment to the specified time 22 day